Quality, Chemical and Microbial Characteristics of Table Eggs at Retail Stores in Baghdad - Al-Obaidi, Faris A.; Al-Shadeedi, Shahrazad M.J.; Al-Dalawi, Rashed H. (International Journal of Poultry Science, 2011)
The objective of this study was to determine the shelf life of marketed table eggs in some retail stores of Baghdad city through determination some quality, chemical and microbial characteristics of the eggs. A total of 1680 chicken eggs (10 eggs were locally produced and 10 eggs were imported) were collected biweekly from retail stores in different seven popular regions of Baghdad city during the period from January 14th to July 15th of 2010. The data obtained revealed that locally produced eggs had lower egg weight, albumen weight and albumen height and higher albumen and yolk pH compared with imported, also Psychrophilic, Coliform, Staphylococci and Fungi counts were high in locally produced eggs compared with imported. No significant differences between locally and imported eggs chemical composition except moisture which was significantly (p<0.05) higher in imported eggs. The total percentage of the incidence of Salmonella in table eggs at retail stores in Baghdad were 20.0% and 38.7% for locally and imported eggs respectively. This survey showed that marketed table eggs in retail stores of Baghdad city were of good quality and within the Iraq standard specification for eggs and where fit for consumption as shell eggs.